MAKANAN ADAT PADA ACARA MANYARATUIH HARI DI NAGARI PAKANDANGAN KECAMATAN ENAM LINGKUNG - Hafazah, Siti; Syarif, Wirnelis; Gusnita, Wiwik (Journal of Home Economics and Tourism, 2015)
The purpose study was (1) to describe the implementation of a series ofceremonies manyaratuih hari, (2) identify the types of traditional food, (3)describe the equipment used to carry traditional food, (4) to know procedure ofserving and structuring, (5) expresses the meaning of traditional food at ceremonymanyaratuih hari. This research descriptive qualitative, the object is customaryfood manyaratuih hari ceremony. The technique of collecting data: observation,interview, and documentation. Data analysis tecniques: data reduction, datapresentation and conclusion of verification. The results showed that manyaratuihhari ceremony consists form any step preparation before the event and the circuitimplementation manyaratuih hari. The food was served, namely food and foodparabuang bajamba, and tools to serve food at the event manyaratuih haricustomary day is dinner plates, cake plates, cups, teapots, kabasuah, tray, trayheight, tuduang saji, dalamak, fabric pambungkuih. Manner of presentation andarrangement of dining, to serve side dishes served on a plate, arranged in the formof jamba, and the feeding by hand. Traditional food at manyaratuih hari event hasmeaning in a relationship friendship, give patience to the bereaved family..Keyword: Traditional food, Manyaratuih Hari